qPCR and loop mediated isothermal amplification for rapid detection of Ustilago tritici - Hanwen Yan; Jian Zhang; Dongfang Ma; Junliang Yin (PeerJ, 2019)
Loose smut of wheat caused by the basidiomycete fungus Ustilago tritici, a seed-borne disease, is difficult to control because of the expanse of wheat planting area and difficulty in pathogen detection. In this study, real-time fluorescence quantitative PCR (qPCR) and loop-mediated isothermal amplification (LAMP) assays are used to rapidly amplify the DNA of U. tritici. Five pairs of primers for qPCR and two series primers for LAMP were designed. Primarily, the specificity of the primer was assessed by using genomic DNA of U. tritici, Fusarium graminearum, Blumeria graminis, Rhizoctonia cerealis, Puccinia striiformis, Bipolaris sorokiniana, and Alternaria solani as templates. Further, the amplification systems were optimized. Finally, the sensitivity of qPCR and LAMP assays were evaluated. The results showed that the primer Y-430 F/R, Y-307 F/R, Y-755 F/R, and Y-139 F/R for qPCR and primers L-139 and L-988 for LAMP could be used for U. tritici detection. In the sensitivity test, the detection limit of qPCR assay was identified as 10 pg μL−1 of genomic DNA, the detection limit for LAMP assay was 100 fg μL−1. We successfully performed qPCR and LAMP assays on wheat loose smut wheat samples. This paper establishes two methods for U. tritici detection, which can be used for diagnosis of wheat loose smut in the laboratory and in the field.